Sharing knowledge about breastfeeding during the COVID-19 pandemic as an influencer in the practice of breastfeeding (Research, Society and Development, 2021)
Introduction: The World Health Organization (WHO) recommends Exclusive Breastfeeding (EBF) up to six months of age, as the primary food for infants, that is, that babies receive only breast milk, without any other type of food during this period. Thinking that breastfeeding is an act that goes far beyond nurturing, diverse knowledge is related to this practice that involves not only the mother and baby, but also the entire support network for this dyad, including health professionals. Objective: Thinking about this set of mother, baby and professional, this study aims to determine the relationship of sharing knowledge between the parties involved for a better practice of breastfeeding. Method: Bibliographic survey of articles and national and international institutional material about the sharing of knowledge in the practice of breastfeeding. Results and Discussion: It was noticed that the sharing of knowledge between nursing mothers and health professionals triggers an adequate support for breastfeeding. Conclusion: when knowledge is shared between the nursing mother and the health professional and using humanized care, the mother is encouraged to breastfeed, resulting in longer periods of maintenance of this practice.